EFFECT OF GOAT MANURE ORGANIC FERTILIZER AND NPK 16-16-16 APPLICATION ON THE GROWTH AND YIELD OF RADISH PLANTS IN SANDY SOIL - Ikhwal, Rival; Hidayati, Nurul; Arfianto, Fahruddin (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Radish (Raphanus sativus) have tubers as a source of carbohydrates, protein, and essential vitamins A and C. This study investigated how the combined application of goat manure and NPK 16-16-16 influences the growth and yield of radish plants when cultivated in sandy soil. The research took place from September 2024 to January 2025 at the Research and Experiment Garden of Universitas Muhammadiyah Palangkaraya (UMPR). The experimental design was a Randomized Block Design (RBD), incorporating two key treatment factors. namely factor I goat manure (K) which consists of 3 levels, namely k1 = 10 tons ha-1, k2 = 20 tons ha-1, k3 = 30 tons ha-1. Factor II NPK 16-16-16 (N) consists of 3 levels, namely n0 = 0 kg ha-1, n1 = 200 kg ha-1, n2 = 400 kg ha-1. The results of the study showed that the interaction of the two treatment factors of goat manure and NPK 16-16-16 did not have a real effect on all observation parameters. Goat manure treatment had a very noticeable effect on the wet weight of the canopy of radish plants at a dose of 20 tons ha-1 (k2) and the treatment of NPK 16-16-16 had a noticeable effect on the wet weight of the canopy at a dose of 400 kg ha-1 (n2) and the fresh weight of radish tubers at a dose of 200 kg ha-1 (n1). It is recommended to cultivate radish plants using a combination of goat manure of 20 tons ha-1 and NPK fertilizer of 400 kg ha-1.